2020
DOI: 10.3389/fncel.2020.612982
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting PNS Plasticity: How Uninjured Sensory Afferents Promote Neuropathic Pain

Abstract: Despite the widespread study of how injured nerves contribute to chronic pain, there are still major gaps in our understanding of pain mechanisms. This is particularly true of pain resulting from nerve injury, or neuropathic pain, wherein tactile or thermal stimuli cause painful responses that are particularly difficult to treat with existing therapies. Curiously, this stimulus-driven pain relies upon intact, uninjured sensory neurons that transmit the signals that are ultimately sensed as painful. Studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…We have also defined that NDT promotes neuronal cell survival in the DRG cultures, speeds up neurites outgrowth and reduces intraneural fibrosis, according to the available evidence reported in the literature on NDT used in clinical and preclinical studies [ 36 , 42 , 48 , 58 , 59 , 78 , 79 , 80 , 81 ]. In addition, our data show that NDT prevents ipsilateral and contralateral mechanical threshold lowering induced by the nerve crush injury, which is a phenomenon sustained by a multilevel PNS plasticity and systemic processes [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have also defined that NDT promotes neuronal cell survival in the DRG cultures, speeds up neurites outgrowth and reduces intraneural fibrosis, according to the available evidence reported in the literature on NDT used in clinical and preclinical studies [ 36 , 42 , 48 , 58 , 59 , 78 , 79 , 80 , 81 ]. In addition, our data show that NDT prevents ipsilateral and contralateral mechanical threshold lowering induced by the nerve crush injury, which is a phenomenon sustained by a multilevel PNS plasticity and systemic processes [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 88%
“…Our data provide evidence that NDT prevents sensitization to normal mechanical stimuli that we observed by the significantly lowered mechanical threshold in the untreated rats on both sides, suggesting that NDT may activate metameric or systemic processes, avoiding nerve sensitization to mechanical stimuli. Even if some pain behaviours related to contralateral DRG changes after a nerve injury, as described in the literature [ 82 , 84 , 85 , 104 ], only a few clinical studies have shown in healthy subjects that NDT improves the mobility of the contralateral untreated limb [ 105 , 106 ]. We provide evidence that NDT administered before nerve injury modulates pain with a significant antiallodynic effect for mechanical stimuli 19 days after nerve injury, with no significant difference in TACAN gene expression in the ipsilateral and contralateral DRG assessed 24 days after the injury when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) ( 21 , 22 ). In neuropathic pain, injured nerves and nonneuronal cells such as glia and mast cells release factors (e.g., substance P, CGRP, bradykinin) that cause uninjured nearby neurons to undergo neurophysiological and neurochemical changes that increase their intrinsic excitability and expression of pain-associated molecules ( 23 ). Signal integration occurs in the spinal cord and involves complex circuits and cell types including numerous excitatory (glutamatergic) and inhibitory (GABAergic and glycinergic) interneurons and descending inhibitory inputs ( 24 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence has suggested that uninjured DRG neurons also play important roles in neuropathic pain, and show robust neurochemical and functional changes after nerve injury (Kalpachidou et al, 2021; Obata et al, 2003; Pertin et al, 2005; Tran & Crawford, 2020). Strikingly, our analysis showed for the first time that uninjured ( Sprr1a − ) neurons in NP1, PEP5, NF1, and NF2 clusters also undergo subtype-specific changes in gene expression after CCI, as compared to those in the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Axotomized neurons may exhibit the most profound gene expression changes that are important for regeneration. Nevertheless, neighboring uninjured DRG neurons also show significant functional changes (e.g., hyperexcitability) and contribute to dysesthesia and evoked pain hypersensitivity as a result of the remaining peripheral innervations (Djouhri et al, 2012; Kalpachidou et al, 2021; Obata et al, 2003; Tran & Crawford, 2020). Details of subtype-specific changes in DRG neurons under neuropathic pain conditions are currently only partially known.…”
Section: Introductionmentioning
confidence: 99%